Strategi Pelestarian Warisan Budaya di Era 4.0: Studi pada Koleksi Langka Perpustakaan dan Museum Sonobudoyo Yogyakarta - Aula Riski, Maydi; Irpina, Wiwin (Nazharat: Jurnal Kebudayaan, 2025)
This paper discusses strategic approaches to the preservation of rare collections in the era of Industry 4.0, with a focus on the Library and Museum Sonobudoyo in Yogyakarta. The study employed a qualitative approach using data collection techniques such as direct observation, in-depth interviews, and document analysis. The findings indicate that the institution has established a written policy on rare collection preservation, structured in the form of Standard Operating Procedures (SOPs). The preservation strategies implemented include: (1) environmental and storage space management supported by Internet of Things (IoT) technology; (2) disaster preparedness systems, including the provision of fire extinguishers (APAR) and the formation of emergency response teams; (3) information preservation through the digitalization of the intellectual content of collections; and (4) cross-sector collaboration and large-scale technological implementation, such as mass deduplication and digitalization. These efforts demonstrate an integration of physical conservation and digital transformation to ensure sustainable access to rare collections amid technologicaladvancements. In conclusion, the preservation of rare collections has been carried out through adaptive, technology-based approaches. These efforts contribute to the sustainability of cultural heritage in the digital era. It is recommended that human resource development and routine evaluation be continuously conducted to maintain the effectiveness of the implemented strategies.